Kajian rintis tentang kesedaran bidang Psikologi Klinikal di kalangan ahli perubatan dan sains kesihatan di Malaysia - Ng, Lai Oon (penerbit ukm, 2007)
Clinical psychology is a specialised field of professional psychology that is much needed with regards to the treatment of mental disorders, behaviour problems and learning difficulties. The field of clinical psychology has been integrated into the health system, especially the mental health and education system, in many western countries. In Malaysia, clinical psychology is still a new concept and has yet to be accepted into the medical and health systems in Jurnal Sains Kesihatan Malaysia 5 (1) 2007: 59-6660 general. This preliminary study looks at the awareness of 199 medical and health sciences professional with regards to clinical psychology. Results of this survey found that only 13.6% of the respondents demonstrated basic knowledge of what clinical psychology is. The awareness of clinical psychology as a clinical profession, and its benefits within the health system is still very much lacking among medical and health sciences professionals. The need to improve awareness of clinical psychology as a clinical profession as well as a health science discipline is very important as clinical psychology services are able to contribute to more holistic treatment of health problems in Malaysia.Implications of this study includes the need for the awareness of clinial psychology to be improved